Fibrinogen gene haplotypes in relation to risk of coronary events and coronary and extracoronary atherosclerosis: The Rotterdam Study - Kardys, Isabella; Uitterlinden, André G.; Hofman, Albert; Witteman, Jacqueline C. M.; de Maat, Moniek P. M. (Thrombosis and Haemostasis, 2007)
Fibrin network structure has been correlated with coronary disease. Fibrinogen γ and α (FGG and FGA) gene haplotypes (chromosome 4q28) may be associated with fibrin network structure, and thereby with rigidity of the fibrin clot and sensitivity of the fibrin clot to the fibrinolytic system. Through these mechanisms they may influence risk of cardiovascular disease. We set out to investigate the relation between combined fibrinogen FGG and FGA gene haplotypes, representing the common variation of the fibrinogen FGG and FGA genes, coronary events and measures of coronary and extracoronary atherosclerosis. The study was embedded in the Rotterdam Study, a prospective populationbased study among men and women aged ≥ 55 years. Common haplotypes were studied using seven tagging SNPs across a 30-kb region with the FGG and FGA genes. Incident coronary events were registered, and carotid intima-media thickness, carotid plaques, ankle-arm index, aortic calcification and coronary calcification were assessed. Seven haplotypes with frequencies >1% covered 97.5% of the genetic variation. In 5,667 participants without history of coronary heart disease (CHD), 733 CHD cases occurred during a median follow-up time of 11.9 years. Fibrinogen gene haplotypes were not associated with coronary events. Fibrinogen gene haplotypes did not show a consistent association with measures of coronary and extracoronary atherosclerosis. In conclusion, fibrinogen FGG and FGA gene haplotypes are not associated with coronary events, coronary atherosclerosis or extracoronary atherosclerosis. Confirmation of these findings by future population-based studies is warranted.
Keywords: Coronary disease; atherosclerosis; epidemiology; genetics; fibrinogen